2014
DOI: 10.1371/journal.pone.0086705
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Small Molecule Interactions between Clinical Isolates of Pseudomonas aeruginosa and Staphylococcus aureus from Adult Cystic Fibrosis Patients

Abstract: Pseudomonas aeruginosa and Staphylococcus aureus are the most prevalent pathogens in airway infections of cystic fibrosis (CF) patients. We studied how these pathogens coexist and interact with each other. Clinical isolates of both species were retrieved from adult CF patients. Culture supernatants from 63 P. aeruginosa isolates triggered a wide range of biofilm-stimulatory activities when added to the culture of a control S. aureus strain. The extent of biofilm formation by S. aureus was positively correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
91
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 59 publications
2
91
0
Order By: Relevance
“…Thus, a large number of quorum sensors act as cell signaling molecules that regulate gene expression within as well as between microbial populations and in the host (345)(346)(347). The extent of biofilm formation and synthesis of pathogenicity factors correlated with species-specific levels of quorum sensors (348)(349)(350). P. aeruginosa quorum sensors were isolated from sputa of CF patients (351,352).…”
Section: Signaling and Virulencementioning
confidence: 99%
“…Thus, a large number of quorum sensors act as cell signaling molecules that regulate gene expression within as well as between microbial populations and in the host (345)(346)(347). The extent of biofilm formation and synthesis of pathogenicity factors correlated with species-specific levels of quorum sensors (348)(349)(350). P. aeruginosa quorum sensors were isolated from sputa of CF patients (351,352).…”
Section: Signaling and Virulencementioning
confidence: 99%
“…This striking negative clinical correlation between S. aureus and P. aeruginosa during teenage years and young adulthood has driven several in vitro and in vivo studies geared toward characterizing the interbacterial interactions of these two organisms (36)(37)(38)(39)(40)(41)(42)(43)(44). These previous studies have found that P. aeruginosa secretes various antistaphylococcal products and proteases, such as LasA, that can cause both biofilm dispersion and cell lysis of S. aureus (42,45).…”
mentioning
confidence: 99%
“…These previous studies have found that P. aeruginosa secretes various antistaphylococcal products and proteases, such as LasA, that can cause both biofilm dispersion and cell lysis of S. aureus (42,45). Further, P. aeruginosa produces several inhibitors of S. aureus respiration, including hydrogen cyanide, quinoline N-oxides, and the phenazine pyocyanin (41,(46)(47)(48). P. aeruginosa has also been described to benefit from coculture with S. aureus by using this Gram-positive organism as an iron source (43) and a cue to produce extracellular virulence factors against both prokaryotic neighbors and the host (49).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, peptidoglycan shed by S. aureus was recently found to stimulate production of virulence factors in P. aeruginosa and thereby increase its lytic activity and virulence in a Drosophila model of infection (1). In addition, P. aeruginosa exoproducts were found to inhibit S. aureus respiration, induce resistance toward antibiotic killing (9), and stimulate pigment (e.g., staphyloxanthin) production, virulence, and biofilm formation by S. aureus (10)(11)(12). The virulence mechanisms of P. aeruginosa and S. aureus and their regulation have been widely studied (13)(14)(15).…”
mentioning
confidence: 99%